If y is a function of x then  (d2y/dx2) + y.(dy/dx) = 0.  If x is a function of y , then what does the same differential equation become ?

2 years ago

Share

Answers : (1)

                                        
Solution:
Let us assume a solution of the original differential equation as:
y=e^{ax}
Hence the given differential equation becomes:
a^{2}e^{ax}+ae^{2ax}=0 \Rightarrow e^{ax}=-a \Rightarrow y=\frac{logy}{x} \Rightarrow y^{1/y}=e^{x}

Thanks & Regards


Sumit Majumdar,


askIITians Faculty


Ph.D,IIT Delhi

6 months ago

Post Your Answer

More Questions On Integral Calculus

Ask Experts

Have any Question? Ask Experts
Post Question
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
evaluate the following integral ∫ sin 2x / a cos^2 (x) + b sin^2 (x) dx
 
 
Ans: Hello student, Please find the answer to your question below
  img
Jitender Singh 3 months ago
Find the following integral ∫dx/(1+(tanx)^1/2) Limit is from pi/6 to pi/3 Please reply soon.
 
 
Dear student, We have the given integral given by: Hence, if we add I twice, we get: Regards Sumit
  img
Sumit Majumdar 5 months ago
 
Ans:Hello student, please find answer to your question …......(1) ......(2) (1) + (2)
  img
Jitender Singh 5 months ago
Calcilate the area bounded between the curves y = x and y = lnx from 0 and 1.
 
 
Ans: Hello Student, Please find answer to your question below y = x y = lnx Area b/w curves ‘A’
  img
Jitender Singh 3 months ago
 
first we should find the area covered by the line in the interval oto1 then we find area covered by the curve lnx in the interval 0 to 1 then the difference gives us the answer
 
pavansai 3 months ago
COS(A-B)/COS(A+B)+COS(C+D)/COS(C-D)=0 THEN SHOW THAT tan A tan B tan C tan D=-1
 
 
STEP1:COS(A-B)/COS(A+B)=(COS(A)COS(B)+SIN(A)SIN(B))/(COS(A)COS(B)-SIN(A)SIN(B)) SIMILARLY OPEN THE EXPRESSION FOR THE OTHER TERM. STEP2:DIVIDE NUMERATOR AND DENOMINATOR IN BOTH CASES BY...
 
siddharth gupta 4 months ago
 
we get tanAtanBtanCtanD=1 not -1
 
Ashish 7 days ago
 
we get tanAtanBtanCtanD=1 not -1
 
Ashish 7 days ago
if sin a, sin b, sin c are in A.P.and cos a, cos b, cos c are in G.P., then the value of (cos^2a + cos^2b – 4cosa cosb) / (1- sina sinb) =
 
 
Hello student, Please find the answer to your question below (cos^2a + cos^2b – 4cosa cosb) / (1- sina sinb) sin a, sin b, sin c…... So, 2 sinb = sin a + sin c…..(1) cos...
  img
Nishant Vora 3 months ago
View all Questions »